2014
DOI: 10.1590/s0036-46652014000100005
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica IN BOVINES IN BRAZIL: DATA AVAILABILITY AND SPATIAL DISTRIBUTION

Abstract: Fasciolosis is a disease of importance for both veterinary and public health. For the first time, georeferenced prevalence data of Fasciola hepatica in bovines were collected and mapped for the Brazilian territory and data availability was discussed. Bovine fasciolosis in Brazil is monitored on a Federal, State and Municipal level, and to improve monitoring it is essential to combine the data collected on these three levels into one dataset. Data were collected for 1032 municipalities where livers were condemn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
4
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 28 publications
0
35
4
7
Order By: Relevance
“…The rivers of these basins flow through the states of Espírito Santo, Minas Gerais and Rio de Janeiro, thus allowing the disease to spread not only in Espírito Santo but also in other states. Bennema et al (2014) reported on occurrences of Fasciola hepatica in cattle in Brazil and observed that in Minas Gerais all the infected municipalities were located in the south of the state. Our results showed the presence of the parasite in the center-south region of the state, again confirming the expansion of fasciolosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rivers of these basins flow through the states of Espírito Santo, Minas Gerais and Rio de Janeiro, thus allowing the disease to spread not only in Espírito Santo but also in other states. Bennema et al (2014) reported on occurrences of Fasciola hepatica in cattle in Brazil and observed that in Minas Gerais all the infected municipalities were located in the south of the state. Our results showed the presence of the parasite in the center-south region of the state, again confirming the expansion of fasciolosis.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, occurrences of this parasite have been reported in the southern, southeastern, central-western and northeastern regions, parasitizing cattle, sheep, buffaloes and wild animals such as coypus and capybaras (SILVA SANTOS et al, 1992;CUNHA et al, 2007;BELLATO et al, 2009;LIMA et al, 2009;CARNEIRO et al, 2010;BENNEMA et al, 2014). Human cases have also been reported in the southern, central-western, southeastern, northeastern and northern regions, with the largest number of cases in the southern and southeastern regions respectively (MAS-COMA et al, 1999;PILE et al, 2000;OLIVEIRA et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…De los resultados del análisis caproparasitologicos (Tabla 1), se puede deducir el carácter de parasitosis de alta prevalencia (74,3%), lo cual se debería a la susceptibilidad de la especie a esta parasitosis, indicaría asimismo, que existen condiciones favorables para la infección o reinfección constante, debido al sistema de alimentación (pastoreo en pasturas deficientes); sabido es que animales bien alimentados, son capaces de limitar su carga parasitaria (Rojas, 2014 Los resultados comparados a nivel nacional, son mayores de los valores encontrados en Oxapampa 10% (Páucar et al, 2010), 36% en Ayacucho (Ticona et al, 2010), 38,2% en Jauja , 24,6% en Aymaraes (Merino y Valderrama, 2017). Asimismo, comparado con otros países, la prevalencia es mayor a lo encontrado en Cuba 3,6% (Godoy et al, 2010), Colombia 3,7-25% (Recalde-Reyes et al, 2014), España 13% (Arias et al, 2012), Huambo, Angola 16,8% , Tabasco, México 11,3% a 31,6 %7% (Alpizar et al, 2013;Ojeda-Robertos et al, 2014), Brasil 0,03-14,39% (Bennema et al, 2014), Colombia 15,5% y 39,4% (Giraldo et al, 2016) y Cuba sobre 50% (Soca-Pérez et al, 2016). Respecto a la prevalencia por sexo y categoría animal (tabla 2), se muestra que los dos sexos y todas las categorías zootécnicas fueron afectadas por esta parasitosis, concordante con Rojas (2004), Ortiz (2011), Valderrama et al (2014), Valderrama (2016).…”
Section: Resultados Y Discusiónunclassified
“…Embora este Estado não seja uma área endêmica para a doença, nos últimos anos com disseminação do hospedeiro intermediário e por consequência de seu parasita, com registro de Lymnaea em Belém (MEDEIROS, 2014). Bennema et al (2014) Fonte: Aleixo et al (2015) De acordo com a figura anterior, para a época descrita, os casos de fasciolose bovina já estão presentes em todas as regiões do Brasil, exceto o Nordeste, com maior incidência para as regiões Sul e Sudeste, onde as condições climáticas são mais favoráveis para o ciclo de vida do parasita.…”
Section: Desenvolvimentounclassified